Analysis of country of origin labeling for food products in Taiwan using auction experiment - Wen S. Chern; Huei-Ching Lin (Osaka University, Institute of Social and Economic Research (ISER), 2010)
The purpose of this study is to evaluate the economic benefits of country of origin labeling (COOL) regulation by estimating the consumer's willingness to pay (WTP) for Taiwan products vs. other imported products if clearly labeled with their countries of origin. We employ the Vickrey second-price sealed bid auction and conducted auctions in three major cities in Taiwan in 2009. Charcoal-smoked plums from Taiwan and China and oolong teas from Taiwan, China, and Vietnam are auctioned products. One important feature of our experimental design is to investigate the impacts of product tasting on bidding behavior. We estimated Tobit bid models and the OLS premium functions. The regression results show that product tasting affected the participants' WTP positively or negatively depending on products. Specifically, tasting raised bids for Taiwan and China teas, but lowered bids for Vietnam tea. The econometric results show very high premiums for Taiwan products, ranging from 83% to 109% for tea and 55% to 66% for charcoal-smoked plum. These findings clearly show strong preference of Taiwanese consumers over food and agricultural products produced domestically. It is very important to have rigorous COOL regulation in Taiwan. If all foods and agricultural products are clearly labeled with their countries of origin, Taiwanese consumers and food producers stand to benefit greatly with COOL. The COOL would be one of the best instruments to reduce the negative impacts of agricultural trade liberalization under WTO or ECFA.
Keywords: Q13; D12; 330; auction experiment; country of origin labeling; Tobit; willingness to pay; bid premium; Taiwan; China; Vietnam; tea; plum; import; food; Ursprungslandprinzip; Willingness to pay; Konsumentenverhalten; Taiwan; China; Auktionstheorie; Test